1997
DOI: 10.1046/j.1365-2567.1997.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of B‐cell activation by the B subunit of Escherichia coli enterotoxin: receptor interaction up‐regulates MHC class II, B7, CD40, CD25 and ICAM‐1

Abstract: SUMMARYThe B subunits of cholera toxin (CtxB) and Escherichia coli heat-labile enterotoxin ( EtxB) are non-toxic lectins that bind and cross-link a ubiquitous cell glycolipid receptor, ganglioside GM1, and are recognized as potent mucosal and systemic immunogens. Here we examine the role of EtxB receptor occupancy in modulating the activation of B cells, in vitro, in primary lymphocyte cultures containing B and T cells. When 48-hr spleen cell cultures containing EtxB were compared with those in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 22 publications
2
72
0
2
Order By: Relevance
“…Binding of CT, LT-I, and LT-IIa, but not binding of LT-IIb, to CD8 ϩ T cells induces apoptosis (2,58). Binding of CT or LT-I to B cells leads to polyclonal activation and to upregulated expression of MHC-II, B7, CD40, CD80, CD86, ICAM-1, and IL-2R␣ (2,36,41). Type I enterotoxins also upregulate expression of CD80 and CD86 on macrophages and dendritic cells (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of CT, LT-I, and LT-IIa, but not binding of LT-IIb, to CD8 ϩ T cells induces apoptosis (2,58). Binding of CT or LT-I to B cells leads to polyclonal activation and to upregulated expression of MHC-II, B7, CD40, CD80, CD86, ICAM-1, and IL-2R␣ (2,36,41). Type I enterotoxins also upregulate expression of CD80 and CD86 on macrophages and dendritic cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Full activation of antigen-specific T cells requires interaction between the T-cell receptor and MHC-II, as well as interaction between CD28 and B7 and/or between CD40 and CD40L on the surfaces of T cells and antigen-presenting cells (APC) (30). Since it was previously reported that CT, LT-I, LT-IIa, and LT-IIb modulate the expression of MHC-II and costimulatory molecules (CD40, CD80, and CD86) on the surface of APC (2,33,36,41), the effects of the mutant enterotoxins LT-IIa(T14S), LT-IIa(T14I), and LT-IIa(T14D) on the levels of expression of CD40, CD80 (B7-1), CD86 (B7-2), and MHC-II on the surfaces of resting B cells (B220 ϩ ) and dendritic cells (CD11c ϩ ) isolated from the spleens of naïve mice were examined.…”
Section: Vol 75 2007 Adjuvanticity Of Mutant Lt-iia Enterotoxins 625mentioning
confidence: 99%
“…CTB triggers the polyclonal activation of B cells. This activation occurs in the absence of significant proliferation and involves the up-regulation of a number of important molecules, namely MHC class II (Ia), B7, CD40, ICAM-1, and IL-2R␣ (CD25) (1,2). CTB induces selective apoptosis of T CD8 ϩ cells.…”
mentioning
confidence: 99%
“…This effect may be due to the activating effect of CTB on B cells, including the up-regulation of MHC class II molecules (12,13). Also involved may be the induction of apoptosis in CD8…”
mentioning
confidence: 99%